"Biggest Thing Is Saying in English and Punjabi, Too": Working with Immigrant and Refugee Families and Communities in a Bilingual Family Literacy Program. Issue 8 (25th August 2021) - Anderson, Jim; Anderson, Ann
Abstract: The purpose of this study, which employed mixed methods, was to document the implementation of a bilingual family literacy program with immigrant and refugee families from four different language groups in five different communities in a metropolitan area of Canada. Results indicated: 1) the program had a significant impact on children's early learning, although there was some variation across sites; 2) families appreciated the bilingual format of sessions and the provision of bilingual materials; 3) parents tended to support first language (L1) maintenance, although some expressed anxiety about their children's English acquisition; and 4) parents expressed concerns, including the need for more explicit instruction, provision of more sessions and a greater focus on school readiness. Although the study indicates the potential of contextually responsive family literacy programs, it also points to the need for nuance and reflexivity on the part of those who work with migrant children and their families.